Ultrafast extreme-ultraviolet photoemission spectroscopy at 18.4 MHz - Heinrich, Stephan; Saule, Tobias; Schötz, Johannes; Lilienfein, Nikolai; Högner, Maximilian; De Vries, Oliver; Plötner, Marco; Weitenberg, Johannes; Esser, Dominik; Schulte, Jan; Russbueldt, Peter; Limpert, Jens; et al. (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
In the past two decades, attosecond science has led to important insights into ultrafast electron dynamics. Whilst extreme-ultraviolet (XUV) photon flux attained from high harmonic generation (HHG) has increased significantly over this time, space-charge effects limit the maximum allowable number of photons per pulse for many attosecond experiments, especially in multidimensional - i.e., either angularly (ARPES) or spatially (PEEM) resolved - photoelectron spectroscopy (PES) on solids [1,2]. To allow for higher average flux without increasing space-charge impairments, HHG sources at higher repetition rates are needed.
CRIS-Team Scopus Importer:2023-04-20